Crowdfunding and the venture creation process - Vergara, Raymond Allan G. (Animo Repository, 2017)
This inquiry explores how crowdfunding affects the venture creation process specifically in the Philippine setting. Using a qualitative, intensive, multi-case based approach, the study traces the progress of four Philippine-based entrepreneurial ventures that began as crowdfunding projects. The progression is then compared to the entrepreneurial venture creation process model developed by Bhave [Journal of Business Venturing, 9(3), 223-242 (1994)]. The study finds that crowdfunding modifies the venture creation process in every stage specified in the model.